Seagrass assisted recovery and long-term monitoring in the Sungai Pulai estuary, Johor, Malaysia - Zakaria, Muta Harah; Syed, Nurul Nur Farahin; Ramaiya, Shiamala Devi; Bujang, Japar Sidik (Frontiers in Conservation Science, 2025)
Seagrass ecosystems in Malaysia are increasingly threatened by coastal development, resulting in widespread habitat degradation. A decade-long monitoring program in the Sungai Pulai estuary (2015–2025) documented trends in species composition, water quality, and habitat recovery following reclamation activities. Thirteen seagrass species were recorded, indicating high diversity compared to the seventeen known in Malaysian waters. Four species, i.e., Halophila decipiens, H. major, H. beccarii, and H. nipponica, were newly documented, with H. nipponica as a new national record for Malaysia. Seagrass percentage cover showed a moderate negative correlation with conductivity (r = –0.622, p < 0.05) in Merambong A (MA), as well as conductivity (r = –0.594), total dissolved solids (r = –0.500), and salinity (r = –0.519) in Merambong C (MC). It also showed a moderate negative correlation with DO (r = –0.545) and salinity (r = –0.502) in Tanjung Adang Laut (TAL). In response to habitat degradation, a rehabilitation program was carried out at the Merambong shoal using Enhalus acoroides seedlings as stabilizer species, along with cover species such as H. ovalis, H. major, and H. spinulosa. A total of 8,591 seedlings were transplanted across 324-square-meter plots, achieving survival rates of 63.39% at MA and 66.07% at Merambong B (MB), surpassing the success of direct seeding and vegetative transplant methods. Cover studies showed that MB consistently had more E. acoroides coverage during the early (10–30 months) and late (30–60 months) stages, peaking at 86.08% in certain plots. The inclusion of mixed species improved sediment stabilization and facilitated rapid vegetative recovery. These findings demonstrate the effectiveness of seedling-based rehabilitation strategies, emphasize the importance of species complementarity, and highlight the need for ongoing monitoring to protect tropical seagrass habitats from human pressures.